2003
DOI: 10.1029/2003gl016887
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of the upper mesosphere temperature above South Pole (90°S): Mesospheric cooling during 2002

Abstract: Polar mesospheric temperature measurements obtained above South Pole from 1991 through 2002 are shown, and their long‐term behavior ‐climatology‐ has been deduced. The variation of this temperature during the polar night shows an annual amplitude of 14 K about the mean yearly value. A strong and highly significant correlation is found between the mean yearly temperature and the solar activity ‐expressed as the F10.7 flux‐, giving a 13 K change per 100 unit F10.7 change. The mean measured 2002 polar night tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 23 publications
(33 reference statements)
9
55
4
Order By: Relevance
“…They also found no connection between the solar 10.7 cm flux (F107) and airglow temperature. This is in contrast to the results of Hernandez [2003], who found a strong correlation with F107. He also suggests a correlation between winter OH* temperatures over the South Pole and the size of the springtime Antarctic ozone hole [Hernandez, 2004].…”
Section: Introductioncontrasting
confidence: 56%
“…They also found no connection between the solar 10.7 cm flux (F107) and airglow temperature. This is in contrast to the results of Hernandez [2003], who found a strong correlation with F107. He also suggests a correlation between winter OH* temperatures over the South Pole and the size of the springtime Antarctic ozone hole [Hernandez, 2004].…”
Section: Introductioncontrasting
confidence: 56%
“…The mesospheric cooling around the major warming is in better agreement between the model (from 185 K on day 265 to 170 K on day 270) and the observation (from 190 K on day to 265 to 170 K on day 275). Above the South Pole, the OH temperature drop (near 85 km) reported by Hernandez [2003] is from 180 K to 168 K (10-day averages) in the period of mid-July and mid-August. The model temperature at 87.5°S and 85 km is in general 40 K warmer than this observation but also displays a cooling of similar magnitude (230 K to 210 K).…”
Section: Time-gcm Analysismentioning
confidence: 99%
“…Mesospheric cooling [Hernandez, 2003;T. D. Kawahara, private communication] and mesospheric jet reversal [Dowdy et al, 2004] were observed above Antarctica prior to the unprecedented major SSW in the Southern Hemisphere (SH) in 2002 [Baldwin et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…These changes can range from the zonal mean wind reversal (Dowdy et al, 2004) to the cooling of the MLT temperature (Hernandez, 2003;Liu and Roble, 2005). Dowdy et al (2004) used three medium frequency (MF) radars located at Davis (69 • S, 78 • W), Syowa (69 • S, 40 • W) and Rothera (68 • S, 68 • W) to study the dynamics of the MLT during the SH 2002 SSW.…”
Section: Introductionmentioning
confidence: 99%